A Codification of the Cubic Projection to Generate Immersive Models (diségno, 2019)
The results of this research aim to describe the representation system made with immersive visualizations. The main goal is to transfer techniques that characterizes immersive models from raster images to models generated with vector images. This way is passed over the boundary that supposes the simple substitution of the elementary geometrical entity, point (or pixel), with the line. In order to do it, the transformations from bi-dimensional views to the immersive panoramic will be codified. It is proposed an advancement for the state of the art, connecting the studies with the descriptive geometry field, opening the cone of vision to the whole space that surrounds the observer. The work considers, as a departure point, previous studies about hybrid immersive models using both equirectangular and cubical projections. But, while for the equirectangular projection there is a complete bibliography for both intuitive (trail-error) and math- ematical methods, for cubical projection instead, the procedures are just approximated, without a necessary theoretical and complete framework. The used method previews, as a mandatory passage, the development of geometrical formulations that will constitute the base for the mathematical ones. Announcing future steps, the content here presented in graphical terms, will look to be synthesized in an algorithm with digital graphics output, written ad-hoc, looking to propose a new advanced technique of representation.
Keywords: cubical projection; cubemap; equirectangular projection; dvanced representation techniques; VR panoramas